2001
DOI: 10.1063/1.1389504
|View full text |Cite
|
Sign up to set email alerts
|

Stark effect and polarizability in a single CdSe/ZnSe quantum dot

Abstract: The quantum-confined Stark effect in a single self-assembled CdSe/ZnSe quantum dot was studied by means of highly spatially resolved photoluminescence spectroscopy. A nanotechnological approach making use of a capacitor-like geometry enabled us to apply a well-defined lateral electric field on the quantum dots. Stark shifts of up to 1.1 meV were obtained, which can be well fitted by a purely quadratic dependence on an electric field. In quite good agreement with theoretical calculations, an exciton polarizabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
76
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 19 publications
9
76
1
Order By: Relevance
“…The fit gives a lateral component of the polarizability = -1.45×10 -3 meV(kV) -2 cm 2 or 20.7 nm 3 in cgs units. This value is of the same order as that obtained for CdSe/ZnSe QDs [56]. It leads to a characteristic lateral dimension of the QD of 2.7 nm which is consistent with the value inferred below from the analysis of the linewidth broadening.…”
Section: Quantum-confined Stark Effect (Qcse)supporting
confidence: 79%
See 1 more Smart Citation
“…The fit gives a lateral component of the polarizability = -1.45×10 -3 meV(kV) -2 cm 2 or 20.7 nm 3 in cgs units. This value is of the same order as that obtained for CdSe/ZnSe QDs [56]. It leads to a characteristic lateral dimension of the QD of 2.7 nm which is consistent with the value inferred below from the analysis of the linewidth broadening.…”
Section: Quantum-confined Stark Effect (Qcse)supporting
confidence: 79%
“…The effects of both lateral and vertical applied electric fields with respect to the QD plane have been studied in several QD structures [54][55][56]. However, only a few recent studies have reported such measurements on GaN/AlN [57,58] and InGaN/GaN QDs [59,60].…”
Section: Quantum-confined Stark Effect (Qcse)mentioning
confidence: 99%
“…This has been observed experimentally in a range of QD systems including InGaAs/GaAs, 29 GaAs/GaAlAs, 30 and CdSe/ZnSe. 31 Furthermore, a theoretical study of an eight-band strain dependent k · p Hamiltonian has shown that the quadratic dependence of the ground-state energy on applied field is a good approximation for largely truncated self-assembled quantum dots, although the approximation becomes worse as the dot size increases in the growth direction. 32 …”
Section: B Excitons and Coulomb Integralsmentioning
confidence: 99%
“…29,30 Upon exposure to oxygen, selenium surface atoms of a CdSe core are photooxidized, creating an evaporating SeO 2 surface film which causes the nanocrystal to degrade over time 31 ( Figure 2A). The increased confinement of excitons broadens the energetic gap between their valence and conduction bands and irreversibly blue shifts their emission wavelength.…”
mentioning
confidence: 99%